Macroalgae as a Source of Valuable Antimicrobial Compounds: Extraction and Applications - Silva, Aurora (2020)
n the last few decades, attention on new natural antimicrobial compounds has arisen due to a change in consumer preferences and the increase in the number of resistant microorganisms. Macroalgae play a special role in the pursuit of new active molecules as they have been traditionally consumed and are known for their chemical and nutritional composition and their biological properties, including antimicrobial activity. Among the bioactive molecules of algae, proteins and peptides, polysaccharides, polyphenols, polyunsaturated fatty acids and pigments can be highlighted. However, for the complete obtaining and incorporation of these molecules, it is essential to achieve easy, profitable and sustainable recovery of these compounds. For this purpose, novel liquid–liquid and solid–liquid extraction techniques have been studied, such as supercritical, ultrasound, microwave, enzymatic, high pressure, accelerated solvent and intensity pulsed electric fields extraction techniques. Moreover, different applications have been proposed for these compounds, such as preservatives in the food or cosmetic industries, as antibiotics in the pharmaceutical industry, as antibiofilm, antifouling, coating in active packaging, prebiotics or in nanoparticles. This review presents the main antimicrobial potential of macroalgae, their specific bioactive compounds and novel green extraction technologies to efficiently extract them, with emphasis on the antibacterial and antifungal data and their applications.